PENGARUH KEPEMIMPINAN, MOTIVASI, DAN REMUNERASI TERHADAP KINERJA ACCOUNT REPRESENTATIVE DI LINGKUNGAN DIREKTORAT JENDERAL PAJAK KANTOR PELAYANAN PAJAK PRATAMA BANTUL - Susanto, Eko; Mahsun, Mohamad; Sulastiningsih, Sulastiningsih (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2025)
The problem in this study is that the Account Representative Performance at KPP Pratama Bantul has not reached the target, resulting in the tax revenue target at the Pratama Bantul Tax Service Office (KPP) in the last 3 (three) years, namely from 2019 to 2021 not being achieved. This study aims to analyze the influence of Leadership, Motivation and Remuneration on the performance of Account Representatives in the Directorate General of Taxes, Bantul Pratama Tax Office. The population in this study were all Civil Servants at KPP Pratama Bantul totaling 94 employees. The sampling technique using purposive sampling technique was selected by all employees except the head of the office and the head of section so that the number of respondents was 79 employees. The data used in this study is a type of quantitative data that can be measured or calculated directly. This study uses data analysis techniques in the form of statistical calculations using SPSS software version 21.0. The results of this study indicate that Leadership, Motivation and Remuneration have a significant influence on employee performance at KPP Pratama Bantul. The results of the hypothesis test show that the three independent variables have a significant positive effect on the independent variables. The greater the Leadership, Motivation and Remuneration provided by the organization, the employee's performance will increase.